2019
DOI: 10.31332/lkw.v5i1.1151
|View full text |Cite
|
Sign up to set email alerts
|

A Correlational Study of Digital Literacy Comprehension Toward Students' Writing Originality

Abstract: This research was aimed to know how far the students’ understanding of digital literacy, to know how high the students’ writing originality, and to know the correlation between students’ understanding of digital literacy and students’ writing originality. Digital literacy is someone’s capability to use the digital device, receive, communicate process, evaluate, and share the information cognitively and technically. Originality is emphasized in writing because it is used as the measurement of the writers’ idea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Besides, the lecturers also introduced students to various types of writing an application to maintain their work originality through some dictionary apps and the magnificent plagiarism checking system. In line with this current research finding, Muthmainnah (2019) revealed a positive correlation between digital literacy understanding and students' writing originality. In addition, Rahman et al (2019) also found that incorporating students with social networking services is a valuable experience to share with the students.…”
supporting
confidence: 89%
“…Besides, the lecturers also introduced students to various types of writing an application to maintain their work originality through some dictionary apps and the magnificent plagiarism checking system. In line with this current research finding, Muthmainnah (2019) revealed a positive correlation between digital literacy understanding and students' writing originality. In addition, Rahman et al (2019) also found that incorporating students with social networking services is a valuable experience to share with the students.…”
supporting
confidence: 89%
“…e rapid development of technology has radically changed the paradigm of how English language teaching is conducted in the twenty-rst century, especially in English as a foreign language (EFL) learning [1][2][3]. One of the shifts brought by the advent of technology is the use of digital games in EFL learning.…”
Section: Introductionmentioning
confidence: 99%
“…[6] His research offers an in-depth study of the concept by analyzing the main models of digital literacy in an international context to offer a holistic model that combines the contributions of all initiatives. His research that students' understanding of digital literacy was good and there was a perfect positive relationship between understanding digital literacy and the originality of student writing [7]. Some of these studies reveal that normal conditions in the use of technology in learning and research can improve digital literacy skills.…”
Section: Introductionmentioning
confidence: 99%